RETRACTED: LncRNA LIPE-AS1 Predicts Poor Survival of Cervical Cancer and Promotes Its Proliferation and Migration via Modulating miR-195-5p/MAPK Pathway - Zhang, Jie; Jiang, Pinping; Wang, Shoyu; Cheng, Wenjun; Fu, Shilong (Frontiers in Oncology, 2021)
Aims: A growing number of studies have unveiled that long non-coding RNA (lncRNA) is conductive to cervical cancer (CC) development. However, the effect of LIPE-AS1 is remained to be studied in CC. Main Methods: Reverse transcription-polymerase chain reaction (RT-PCR) was employed to measure LIPE-AS1 expression in CC tissues and the adjacent normal tissues. Additionally, we conducted gain- and loss-of functional experiments of LIPE-AS1 and adopted CCK8 assay, BrdU assay, and in vivo tumor formation experiment to test the proliferation of CC cells (HCC94 and HeLa). Besides, the apoptosis, invasion, and epithelial-mesenchymal transformation (EMT) of CC cells were estimated using flow cytometry, transwell assay, and western blot, respectively. Further, LIPE-AS1 downstream targets were analyzed through bioinformatics, and the binding relationships between LIPE-AS1 and miR-195-5p were verified via dual-luciferase activity experiment and RNA Protein Immunoprecipitation (RIP) assay. Moreover, rescue experiments were conducted to confirm the effects of LIPE-AS1 and miR-195-5p in regulating CC development and the expressions of MAPK signaling pathway related proteins were detected by RT-PCR, western blot, and immunofluorescence. Key Findings: LIPE-AS1 was over-expressed in CC tissues (compared to normal adjacent tissues) and was notably related to tumor volume, distant metastasis. Overexpressing LIPE-AS1 accelerated CC cell proliferation, migration and EMT, inhibited apoptosis; while LIPE-AS1 knockdown had the opposite effects. The mechanism studies confirmed that LIPE-AS1 sponges miR-195-5p as a competitive endogenous RNA (ceRNA), which targets the 3′-untranslated region (3′-UTR) of MAP3K8. LIPE-AS1 promoted the expression of MAP3K8 and enhanced ERK1/2 phosphorylation, which were reversed by miR-195-5p. Significance: LIPE-AS1 regulates CC progression through the miR-195-5p/MAPK signaling pathway, providing new hope for CC diagnosis and treatment.